2021
DOI: 10.3310/nihropenres.13215.1
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre review comparing long term outcomes of endoscopic vein harvesting versus open vein harvesting for coronary artery bypass surgery

Abstract: Background: Utilisation of the Endoscopic Vein Harvesting (EVH) technique has been increasing for coronary artery bypass grafting (CABG) for the last two decades. Some surgeons remain concerned about the long-term patency of the long saphenous vein harvested endoscopically compared to traditional Open Vein Harvesting (OVH). The aim of this study was to perform a retrospective analysis of the outcomes between EVH and OVH from three UK centres with 10 years follow-up. Methods: 27,024 patients underwent CABG with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, a large retrospective multicenter analysis has indicated that EVH has a lower risk of mortality compared to OVH over a follow-up period of six years. Although our study did not include an extended follow-up period, similar findings are expected from this cohort as reported in other studies [22].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, a large retrospective multicenter analysis has indicated that EVH has a lower risk of mortality compared to OVH over a follow-up period of six years. Although our study did not include an extended follow-up period, similar findings are expected from this cohort as reported in other studies [22].…”
Section: Discussionsupporting
confidence: 90%
“…In this era, with gradual increase in the use of a no-touch technique [ 10 , 11 ], the importance of managing vein harvest site complications should be emphasized [ 12 ]. Although endoscopic vein harvest has several benefits for wound complications and cosmetic aspects, there is still some debate about graft patency and clinical outcomes [ 13 , 14 ]. Kim et al [ 9 ] suggest that the use of a drainage tube in the no touch harvesting site is important in reducing complications associated with leg wounds.…”
Section: Discussionmentioning
confidence: 99%
“…In this era, with gradual increase in the use of a no-touch technique [8, 9], the importance of managing vein harvest site complications should be emphasized [10]. Although endoscopic vein harvest has several bene ts for wound complications and cosmetic aspects, there is still some debate about graft patency and clinical outcomes [11,12].…”
Section: Discussionmentioning
confidence: 99%